China’s Efforts to Control the Arctic Rimland: A New Cold War - Fragkouli, Marina (HAPSc Policy Briefs Series, 2021)
In 2018, China released the much-expected White Paper and its Arctic policy in the region. China foresees the economic opportunities and realizes the territorial challenges as it seeks an active role in the Arctic opening. The White Paper outlines China’s aspirations and strategies to develop the Polar Silk Road across the Arctic Ocean. As a non-Arctic state and without a claim of territory, China will likely have to rely on cooperation and invitation of Arctic states so as to advance its interests in that area. This policy brief outlines China’s interests in the region as well as the socio-economic and environmental challenges that will be called to manage. Moreover, it examines the probability to be declared a greater Arctic player through the emergence of the Polar Silk Road and possible shifts in the current status quo and the balance of power in the region. Thus, taking all these into account it briefly suggests four possible measures.